Предмет: Алгебра, автор: tvobzorshik

1) (3✓2+1)(✓8-2)
2) (3-2✓7)²+(3+2✓7)²
Отдам все балы за это

Ответы

Автор ответа: oksik1970
1

Ответ:

1)

10 - 4 \sqrt{2} \:  \\

2)

74

Объяснение:

1)

(3 \sqrt{2}  + 1)( \sqrt{8}  - 2) = (3 \sqrt{2}  + 1)(2 \sqrt{2}  - 2) = 3 \sqrt{2}  \times 2 \sqrt{2}  - 6 \sqrt{2}  + 2 \sqrt{2}  - 2 = 12 - 4 \sqrt{2}  - 2 =  10 - 4 \sqrt{2}  \\

2)

 {(3 - 2 \sqrt{7}) }^{2}  +  {(3 + 2 \sqrt{7} )}^{2}  = 9 - 12 \sqrt{7}  + 28 + 9 + 12 \sqrt{7}  + 28 = 74 \\

Похожие вопросы